Kandahar Province In the political and military conflict between India and Iran during the reign of Shah Jahan Mughali (1628-1658) - Mustafa Muhammad karem (QALAAI ZANIST JOURNAL, 2022)
The political relations of each country at a certain historical stage can be a criterion for knowing the strength and weakness of that state in the fields (political, economic, or military). The Indian Mughal Empire during the reign of Shah Jahan had the lowest relations with neighboring countries on a general level and with the Safavid state on a Private level.The relations between the two countries over Kandahar deteriorated to the point of reaching a military confrontation, and although the result of the military confrontations was not reassuring for Shah Jahan from the political and military sides, he did not despair throughout his reign from his attempts to persist in the confrontation to control Kandahar, and this It is one of the prominent political features of his reign.The research included dealing with special features related to Kandahar in terms of the importance of the city and the reasons behind the interest of the Indian Mughal Empire in this city and clarifying the challenges and developments of the war on the city during the reign of Shah Jahan. This study consists of four axes, the first axis entitled (The Indian Mughal Empire’s control of Kandahar in the year 1638) and sheds light on the city of Kandahar and its importance for the Mughal Indian Empire and the Safavid state, both economically and militarily, and then emphasizing the role of (Ali Mardan Khan Zik) in handing over Kandahar to the Mughal Indian Empire, and at the end of the axis, the political and military challenges that faced both countries after controlling Kandahar were highlighted. As for the second axis, it was devoted to discussing the conditions of the city of Kandahar during the period in which calm prevailed between the Mughal Indian Empire and the Safavid state. In the beginning, the political and diplomatic steps of Shah Jahan were discussed regarding his attempts to reduce tension in his relations with the Safavid state after the death of Shah Safi I, especially In the fourth year of the reign of Shah Abbas II.As for the third axis entitled the Safavid state’s control of Kandahar in 1649, in this axis, the military steps of Shah Abbas II were discussed with the aim of returning the Kandahar state to the grip of the authority of the Safavid state.In the fourth axis and at the end of the study, the trends and developments of the war in Kandahar and its surrounding areas were highlighted after it returned to the rule of the Safavid state and its effects, as well as the desperate attempts of Shah Jahan to restore his power throughout his reign. Key word: Kandahar, Indian Mughal Empire, Safavid, Shah Jahan Mughali, shah Abbas II, politics, relations.